ANALISIS FUNGSI DOMPET DIGITAL TERHADAP PENINGKATKAN KINERJA KEUANGAN UMKM JUMPUTAN PALEMBANG - Djumrianti, Desloehal (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of this study is to analyse the function of digital wallets on improving the financial performance of Palembang Jumputan MSMEs. A total of 33 Palembang Jumputan MSMEs were the object of this study. Data collection techniques were conducted by semi-structured interviews with key informants or Palembang Jumputan sellers. This research is qualitative descriptive using a case study approach. The study results show that the function of digital wallets can support the improvement of the financial performance of Palembang jumputan MSMEs, this can be seen from the capital adequacy ratio, liquidity ratio and good profitability ratio. This research is expected to be useful for other MSMEs in using digital wallets. Keywords: digital wallets, MSMEs of Jumputan Palembang, financial performance